The Canadian Labour Congress and Tripartism - Giles, Anthony (Relations industrielles / Industrial Relations, 1982)
After having addressed the concept of tripartism and the issues of corporatism and incomes policies, the author examines the background to the imposition of controls and the subsequent tripartism debate. Finally, the author focuses on the main stages in the negociations over controls and tripartism, with particular reference to major shifts in CLC policy and strategy.